Effects of the removal of vision on body sway during different postures in elite gymnasts - Asseman, F.; Caron, O.; Cremieux, J. (International Journal of Sports Medicine, 2005)
The aim of this study was to analyse the effects of the removal of vision on postural performance and postural control in function of the difficulty and specificity of the posture. Twelve elite gymnasts were instructed to be as stable as possible with eyes open and eyes closed in three postures: bipedal, unipedal, and handstand ranked from the less difficult and less specific to the more difficult and more specific. The ratios eyes closed on eyes open, computed on CP surface and CP mean velocity, which respectively represents postural performance and postural control, were similar in the bipedal and handstand postures. They were highly increased in the unipedal one. The effect of the removal of vision and so the role of vision on body sway was not directly linked to the difficulty or specificity of the posture; other tasks' characteristics like the segments configuration also played a role.